Pelatihan Pembuatan Kerajinan Tangan Bros dari Kain Perca pada Ibu-Ibu PKK Sebagai Agen Wanita Pancasila: Meningkatkan Kreativitas dan Pemanfaatan Limbah Konveksi - Fitri Rohani; Umi Endah Nur Aini (Universitas Negeri Semarang, 2026)
The Real Work Lecture (KKN) aims to apply theory in direct practice for the community, including in waste management. This research focuses on training in making brooches from patchwork, convection waste that is often not used. This activity was carried out in Bantengan Village, targeting PKK women who have high creative potential. The training method involves socialization, demonstrations, and direct mentoring to teach techniques for making brooches from patchwork. The training process includes the presentation of material about materials and tools, manufacturing demonstrations, and practice with guidance. The result of this training is various brooch designs that show the creativity of the participants, as well as the use of patchwork waste that can reduce environmental pollution. This activity has succeeded in improving the skills and creativity of PKK women, opening up new business opportunities, and supporting local economic empowerment, although long-term monitoring of business development is still needed.